The Role of Cell Blocks and Immunohistochemistry in Thyroid Atypia of Undetermined Significance/Follicular Lesion of Undetermined Significance Bethesda Category - Abram, Mikk; Huhtamella, Roope; Kalfert, David; Hakso-Mäkinen, Heli; Ludvíková, Marie; Kholová, Ivana (Acta cytologica, 2021)
INTRODUCTION: Thyroid cytology is a widely accepted tool in the clinical triaging of nodular lesions. Cell blocks (CBs) can help in the diagnosis of atypical lesions, namely, thyroid Bethesda category of Atypia of undetermined significance/follicular lesion of undetermined significance (AUS/FLUS). METHODS: In a series of 224 AUS/FLUS thyroid samples with CB, we studied CB cellularity and feasibility of 3 immunohistochemical markers (cytokeratin 19 [CK19], HBME-1, and galectin-3) apart and in combination. RESULTS: The CBs were non-diagnostic in 34 cases. Twenty-four CBs contained <10 cells, 45 CBs 10-50 cells, and 121 CBs >50 cells. Notably, more cellularity was found in CBs performed by plasma-thrombin and in-house techniques (p < 0.001). The diagnostic accuracy to detect malignancy was 65.1% for CK19, 72.1% for HBME-1, and 70.3% for galectin-3. CONCLUSION: In conclusion, CB cellularity is essential for successful immunohistochemistry application and further diagnostic workup of AUS/FLUS cases.
Keywords: Tissue Fixation; Humans; Cell block; studie proveditelnosti; Predictive Value of Tests; zalévání tkání do parafínu; Biomarkers, Tumor; HBME-1; Thyroid Neoplasms; krevní proteiny; lidé; Cytokeratin 19; Galectins; Immunohistochemistry; imunohistochemie; reprodukovatelnost výsledků; galektiny; nádorové biomarkery; Blood Proteins; Neoplasm Grading; Reproducibility of Results; prediktivní hodnota testů; Retrospective Studies; fixace tkání; stupeň nádoru; Paraffin Embedding; Galectin-3; Keratin-19; nádory štítné žlázy; retrospektivní studie; keratin-19; Feasibility Studies; Thyroid gland